2020
DOI: 10.18231/j.ijmr.2020.005
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge attitude and practices of biomedical waste management among medical and nursing students in a teaching hospital of J & K, India

Abstract: Biomedical waste (BMW) management means to reduce waste generated from healthcare facilities and effectively segregate, collect, transport and dispose it in such a way that it is no more hazardous to HCW (healthcare workers), community or the environment. Lack of awareness and inadequate knowledge about BMW management can have serious consequences. To assess and compare the Knowledge, attitude, practices (KAP) of BMW management among medical and nursing students. A cross sectional study was don e at a tertiary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
1
3
0
1
Order By: Relevance
“…[7] The practices among nursing students regarding biomedical waste management were excellent which was in contrast with studies that showed poor pattern of practices among nurses and nursing students. [10,16] Other studies conducted among nurses showed good level of practice among nurses which was in line with the present study. [7,11,13,17] In our study, about 40% of nursing students reported unsafe practices of recapping used needles which may expose them to needle stick injury.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…[7] The practices among nursing students regarding biomedical waste management were excellent which was in contrast with studies that showed poor pattern of practices among nurses and nursing students. [10,16] Other studies conducted among nurses showed good level of practice among nurses which was in line with the present study. [7,11,13,17] In our study, about 40% of nursing students reported unsafe practices of recapping used needles which may expose them to needle stick injury.…”
Section: Discussionsupporting
confidence: 92%
“…[4,18] Nursing students had an excellent attitude regarding biomedical waste management which is comparable to studies among nursing students. [5,10] Studies conducted among nurses and health care workers also showed positive attitude [11,15,17] while negative attitude was also shown Vol.11; Issue: 9; September 2021 among nurses. [3] A study reported poor attitude among resident doctors regarding biomedical waste management in comparison to nursing staff.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Konu ile ilgili bazı araştırma sonuçları çalışmamızla benzerlik gösterirken 22,25 ; bazı araştırmalarda öğrencilerin atık torbalarına ilişkin bilgi düzeyinin yetersiz olduğu görülmektedir. 26,27 Fauzi ve Dahari (2019) tarafından hemşirelik öğrencilerinin biyomedikal atık yönetimine yönelik bilgi, tutum ve uygulamalarını değerlendirmek amacıyla yapılan araştırmada öğrencilerin büyük çoğunluğunun atık torbaları ile ilgili bilgi düzeyinin yeterli olduğu saptanmıştır. 22 Abou Hashish ve arkadaşları (2020) tarafından yapılan araştırmada ise katılımcıların atık torbalarının renklerini bilme düzeyinin yetersiz olduğu bulunmuştur.…”
Section: Araştırmanın Evren Ve öRneklemiunclassified